Adherence to pharmacological and nonpharmacological treatments in adults with type 2 diabetes - Coelho Gomes, Andreia; Amanne Medeiros Ribeiro, Gabriela; Seabra Moraes, Mikael; Cristina de Miranda Gonçalves, Isabela; de Almeida Gonçalves Sachett, Jacqueline (O Mundo da Saúde, 2020)
Treatment in diabetes is basically performed by pharmacological and nonpharmacological (physical activity and nutrition) therapies. However, adherence to treatment is a constant challenge, requiring a greater understanding and direction of the multiple aspects that can interfere with adherence to these different types of treatment. Therefore, the study sought to estimate the prevalence of aspects that influence adherence to pharmacological and nonpharmacological treatments of people living with type 2 diabetes. This was a descriptive and cross-sectional study, with 139 users, registered and participating in programs aimed at the diabetic population in a Basic Family Health Unit in the city of Manaus, Amazonas, Brazil. Data were collected through an interview using a semi-structured form with questions related to sociodemographic, economic, clinical and health aspects in general, and pharmacological and nonpharmacological treatments (physical activity and nutrition). The prevalence of adherence to pharmacological treatments was the highest (74.8%), followed by adherence only to physical activity (56.1%). There was a low prevalence of adherence only to nutrition (10.2%). When estimating the combined prevalence, pharmacological treatments associated with physical activity was the most prevalent (40.3%). The combined adherence between pharmacological and nonpharmacological treatments (physical activity and nutrition) was low (5.8%). The study concludes by reinforcing that the action of the multiprofessional health team is a fundamental tool that acts with a comprehensive approach to promoting, preventing and maintaining health and that it can contribute to greater adherence to the treatment of users with type 2 diabetes.